Unpublished Palinological Records in the Teresina and Rio do Rasto Formations (Permian, Passa Dois Group, Paraná Basin) Biocostratigraphic and Paleoenvironmental Implications - Neregato, Rodrigo [UNESP]; DE SOUZA, Paulo Alves; Rohn, Rosemarie [UNESP] (Universidade Federal do Rio Grande do Sul, 2008)
The Pennsylvanian-Permian interval of the Paraná Basin is relatively well-known on its palynological content. However, little has been published from the Permian Serra Alta, Teresina and lower Rio do Rasto formations (Passa Dois Group). A total of thirty seven core samples were collected along a vertical range of 600 meters of these units in two boreholes in the Congonhinhas Municipality, northeastern Paraná State, South Brazil, but only the Teresina Formation and the lower part of the Serrinha Member of the Rio do Rasto Formation yielded identifiable palynomorphs. Of the thirty recorded species, ten species are registered for the first time in the basin, three are probably new, and five were previously documented at stratigraphic levels below the units of the present study. Assemblages are assigned to the Lueckisporites virkkiae Zone, regarded as Middle Permian (Guadalupian) in age, as suggested by other fossil and radiometric data. According to the relative abundance of some spore species, it is possible to discriminate two intervals: the first characterized by the predominance of Laevigatosporites vulgaris (from the Teresina Formation to the basal Serrinha Member), and the second dominated by Thymospora (in higher stratigraphic levels). The great abundance of fern spores in these assemblages is amazing because lycophyte stems are the best represented macrophytofossils of the Teresina Formation, similarly as glossopterid leaves and sphenophyte stems in the Rio do Rasto Formation. These aspects are discussed in the scope of lithofaciological and other paleontological data.
Registros Palinológicos Inéditos nas Formações Teresina e Rio do Rasto (Permiano, Grupo Passa Dois, Bacia do Paraná) Implicações Biocronoestratigráficas e Paleoambientais
Keywords: Palynology; Paraná Basin; Permian